The Yin and Yang of Decision Making: Strategic Planning and Improvisation in an Entrepreneurial Culture - Anton Fenik; Ernest R. Cadotte; Helena F. Allman (Journal of Applied Marketing Theory)
Only a few empirical studies examine the influence of organizational improvisation on firm performance. Further, more insight is needed regarding the coexistence of normative (i.e., planned) and descriptive (i.e., improvised) forms of decision-making. This paper contributes to the literature by filling these gaps. It investigates the moderating effect of entrepreneurial behaviors on the relationship between improvisation and firm performance. It explores whether improvisational decision-making can improve firm performance beyond planning’s effect on firm outcomes. We employ decision theory and sensemaking literature in our conceptual model. We test our hypotheses with data from a cross-sectional managerial survey and a behavioral simulation involving a new product development context. The results reveal a positive moderating effect of entrepreneurial behaviors on the relationship between improvisation and firm performance and that organizational improvisation positively affects firm performance beyond the effect of formal planning.